The predictors to self-reported and performance-based physical function in knee osteoarthritis patients: a cross-sectional study - Wang, Qian-wen; Man, Gene Chi-wai; Choi, Ben Chi-yin; Yeung, Yi-man; Qiu, Ji-hong; Lu, Xiao-min; Ong, Michael Tim-yun; Yung, Patrick Shu-hang (Frontiers in Cell and Developmental Biology, 2024)
Background Osteoarthritis (OA) knee patients have limited ability in physical function, or difficulties with physical tasks and activities may develop disability. This study aimed to observe the predictors of self-reported and performance-based physical function in patients with knee OA by analyzing the impacts of demographic, pathological, and muscle impairment factors. Methods 135 knee OA patients participated in this study to complete self-reported questionnaires using Knee Injury and Osteoarthritis Outcome Score (KOOS). When measuring performance-based physical function, a 6-meter gait speed (6MGS) test was measured to evaluate their mobility, and a 5-time Sit-to-Stand test (5STS) was assessed to evaluate their balance. Pain intensity, knee extensor and flexor muscle strength, age, body mass index (BMI), durations of symptoms, and radiographic severity were also collected. Spearman correlation and stepwise multiple linear regression were used to explore the association and predictors in self-reported and performance-based physical function. Results BMI and durations of symptoms did not indicate any significant correlation with either self-reported or performance-based physical function. Age is significantly negatively associated with 6MGS (r2 = −0.383, p < 0.01), while knee extensor muscle strength has a moderate correlation with 5STS (r2 = −0.528, p < 0.01). In the stepwise multiple linear regression models, pain intensity (β = 0.712, p < 0.001), knee flexor muscle strength (β = 0.112, p = 0.042) were significantly associated with self-reported physical function in daily activities and contributed to 55.0% of the variance in KOOS-PF score. Knee muscle strength, including knee extensor (5STS: β = −0.428, p < 0.001) and flexor muscle strength (6MGS: β = 0.367, p < 0.001), were the main predictors with performance-based physical function. Conclusion Pain intensity was the leading risk factor of self-reported physical function, and knee flexor muscle strength contributed as well. The severity of knee OA, durations of symptoms and BMI did not contribute to physical function. However, knee extensor and flexor muscle strength were the main predictors of performance-based performance. Our results show that strengthening of weak knee muscles in both quadriceps and hamstring muscle strength should be considered a priory consideration in knee OA no matter if people are in the early or end-stage of knee OA.